THE EDUCATION OF WOMEN IN ETIflOPIA: A MISSING PIECE IN THE DEVELOPMENT PUZZLE - Seyoum, Teferra (The Ethiopian Journal of Education, 2024)
Today educatiol/(/I disparity between the sexes is one of the critical Issues in the development of education in the Third World Countries. This hort article surveys the status of women's education in Ethiopia prior to 1974. Attempt is made to show that in traditional Ethiopia women had heen excluded from getting church and koranic education. and al 'o 'illce the introduction of modern education into the country. at the turn of the century, their participation rate at the various levels of the educational system has been very minima/. Furthermore, the study tries to highlight that the participation of women in education is a criticalfactor in the development equation